Serum Micronutrient Status of Haart-Naïve, HIV Infected Children in South Western Nigeria: A Case Controlled Study - H. C. Anyabolu; E. A. Adejuyigbe; O. O. Adeodu (AIDS Research and Treatment)
Background. Though micronutrients are vital in the pathogenesis of human immunodeficiency virus infection, most studies have been conducted in adults. Knowledge of the status of key micronutrients in HIV infected African children will indicate if supplementation may be beneficial to these children living in this resource-poor region. Objectives. We sought to determine the micronutrient status and associated factors of HAART-naïve HIV infected children and compare them with those of the HIV negative controls. Methods. We enrolled 70 apparently stable HAART naïve HIV infected children. Seventy age and sex matched HIV negative children were equally enrolled as the controls. Their social class, anthropometry, clinical stage, CD4 counts, serum zinc, selenium, and vitamin C were determined. Results. The prevalence of zinc, selenium, and vitamin C deficiency in HIV infected subjects was 77.1%, 71.4%, and 70.0%, respectively, as compared to 44.3%, 18.6%, and 15.7% in HIV negative controls. Among the HIV infected subjects, 58.6% were deficient in the three micronutrients. Micronutrient status was related to the weight, clinical, and immunological stages but not BMI or social class. Conclusion. Deficiency of these key micronutrients is widely prevalent in HAART naïve HIV infected children irrespective of social class. This suggests that supplementation trial studies may be indicated in this population.